2019
DOI: 10.17582/journal.sajls/2019/7.1.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Rate on the Growth, Feed Efficiency and Composition of Hoplobatrachus Occipitalis (Günther, 1858) Tadpoles’ Carcass in Controlled Medium

Abstract: The current study aims at evaluating the effect of experimental feed protein rate on growth and feed utilization in Hoplobatrachus occipitalis tadpoles. Six same-energy feed diets containing crescent protein rates (20, 30, 40, 45, 50 and 60 %) were formulated and tested on Hoplobatrachus occipitalis tadpoles though initial mean weight was 0.380 ± 0.004 g. Each diet was tested in triplicate for 24 days. 55 tadpoles was stocked per pond containing 30L water. Survival rates recorded ranged between 85.454 and 92.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
(12 reference statements)
0
3
1
Order By: Relevance
“…In this study, the survival rates of frogs fed different feed types were 56.00-64.67%. This rate seemed lower than that in previous studies on frogs, mostly tadpoles (Sretarugsa et al, 1997;Olvera-Novoa et al, 2007;Mustapha & Bello, 2018;Godome et al, 2019). However, it should be noted that the results have depended on several factors, such as species, stocking density, and environmental conditions (Hafedh, 1999).…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…In this study, the survival rates of frogs fed different feed types were 56.00-64.67%. This rate seemed lower than that in previous studies on frogs, mostly tadpoles (Sretarugsa et al, 1997;Olvera-Novoa et al, 2007;Mustapha & Bello, 2018;Godome et al, 2019). However, it should be noted that the results have depended on several factors, such as species, stocking density, and environmental conditions (Hafedh, 1999).…”
Section: Discussioncontrasting
confidence: 65%
“…The protein content of the feed is significant for weight gain in frogs. According to studies on frog diets, the protein ratio suitable for tadpole and juvenile stage growth and development should be 40% (Carmona-Osalde et al, 1996;Olvera-Novoa et al, 2007;Godome et al, 2019). However, Browne (2009) discovered that proteins alone do not determine the growth performance of frogs under culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an ectothermal animal, tadpoles kept under a high interval of thermal discomfort do not develop (Knoop et al, 2015;Godome et al, 2018), as this parameter directly influences food consumption caused by thermal stress, compromising the healthy development of these animals (Braga & Lima, 2001). This can be confirmed in the study by Hoffmann et al (1988), which observed that the tadpoles presented higher biomass and less time to complete metamorphosis when kept at elevated temperatures, with the ideal temperature around 25 ºC.…”
Section: Introductionmentioning
confidence: 70%